Going from embryo to adult: How zebrafish zic genes are regulated during development - Holman, Nathanael Thomas (My University, 2009)
This project aims to further our understanding of developmental genetics by identifying unknown transcription factor binding sites that play an important role in regulating zic2a, a gene required for proper neural development in vertebrates. To do this, transgenic zebrafish were created that have various versions of the zic2a gene coupled with green fluorescent protein coding sequence. The transgenes differ by a single mutation in one of the several evolutionary conserved sequences in the enhancer region, which are thought to be transcription factor binding sites. By comparing the expression patterns of the green fluorescent protein among the transgenic zebrafish I identify sites that are required for zic2a transcription during development.
12 p.
Keywords: Zoology; Genetics